Water Quality and Fish Species Diversity of Kabul River at Darounta Dam, Nangarhar Afghanistan (International Journal of Scientific Research and Management (IJSRM), 2025)
Water is most abundant fluid covering about 70% of earth surface. Water quality at the origin of source is usually better due to heavy rainfall, Physical characteristics of water (temperature, color, taste, odor etc.) are determined by senses of touch, sight, smell and taste. The chemical characteristics of natural water are reflection of the soils and rocks with which the water has been in contact. Afghanistan is located in central Asia. The area is 652,000 square originates from Paghman Mountains in Afghanistan and flows for about 480 km before joining River Indus at Attack in Pakistan. Kabul river basin draining to the Indus River with 44 fish species. In these fish species family Cyprinidae was found the richest one overall